2021
DOI: 10.1098/rspa.2021.0311
|View full text |Cite
|
Sign up to set email alerts
|

Post-bifurcation behaviour of elasto-capillary necking and bulging in soft tubes

Abstract: Previous linear bifurcation analyses have evidenced that an axially stretched soft cylindrical tube may develop an infinite-wavelength (localized) instability when one or both of its lateral surfaces are under sufficient surface tension. Phase transition interpretations have also highlighted that the tube admits a final evolved ‘two-phase’ state. How the localized instability initiates and evolves into the final ‘two-phase’ state is still a matter of contention, and this is the focus of the current study. Thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…In the previous section, a detailed analysis of the bifurcation threshold for localized necking/bulging of a residual stressed hyperelastic cylinder under extension has been presented. We found that different loading scenarios share the same bifurcation condition, consistent with the findings reported in Fu et al [35], Emery and Fu [36], Ye et al [41], and Emery and Fu [61].…”
Section: The Maxwell Equal-area Rulesupporting
confidence: 91%
See 3 more Smart Citations
“…In the previous section, a detailed analysis of the bifurcation threshold for localized necking/bulging of a residual stressed hyperelastic cylinder under extension has been presented. We found that different loading scenarios share the same bifurcation condition, consistent with the findings reported in Fu et al [35], Emery and Fu [36], Ye et al [41], and Emery and Fu [61].…”
Section: The Maxwell Equal-area Rulesupporting
confidence: 91%
“…Surface tension and residual stress play similar roles when evaluating their influence on generating localized instabilities. Fu et al [35] and Emery and Fu [36, 61] report that for fixed axial length localized bifurcation occurs when d N / d λ = 0 . Therefore, we may assume that the bifurcation condition is again given by equation (91) with the residual stress magnitude ν (or κ ν 2 ) now being the independent loading parameter.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognizing that localized bulging is a 'zero wavenumber' bifurcation phenomenon, recent studies have examined the weakly nonlinear near-critical behaviour [38] and the effects of rotation, fibre-reinforcement, tethering and multi-layering on bulge initiation [39][40][41][42][43]. The methodology developed has also been extended to studying surface tension-induced necking [44][45][46][47]. The commonly used approach of modelling localized bulging/necking as a 'finite wavenumber' bifurcation phenomenon has been appraised in a recent study [48].…”
Section: Introductionmentioning
confidence: 99%